The Evaluation of Online Learning During the Covid-19 Pandemic Among the Accounting Students of Universitas Tarumanagara - Amin Wijoyo; Nastasya Cindy (Graduate Program of Universitas Tarumanagara, 2023)
Corona outbreak has changed daily life and of course the Education department is also affected. Before corona, learning was done face-to-face, but now learning must be carried out online. This study was conducted to evaluate online learning during the pandemic for accounting students at Universitas Tarumanagara. The data was taken from a questionnaire for accounting students at Universitas Tarumanagara who took part in online learning. Data were taken from all active accounting students at Universitas Tarumanagara. The things which might be evaluated are the level of student satisfaction in online learning, the online learning media used, the delivery of teaching materials in online learning, deficiencies in online learning, and student choices in the lecture method.